The BC SUPPORT Unit Data Platform: Offering Data-Related Services To Researchers In British Columbia. (2018) - Kesselring, Sarah; Mander, Bryony; Djurdjev, Ognjenka; Moselle, Kenneth; Portales-Casamar, Elodie; Schuckel, Victoria; Singer, Joel; Sobolev, Boris; Wong, Shirley; Brasher, Penny; Cherban, Erin; Young, Ella; et al.
No abstract available